Strategy and Redefinition of Ambient Media Advertising in the Digital Age: Theoretical Review with Conceptual Contributions - Firmanda Satria; Acep Iwan Saidi; Agung Eko Budi Waspada; Kunto Adi Wibowo (International Journal Labs, 2026)
Ambient media advertising has evolved significantly from its traditional, physically focused origins, yet a comprehensive theoretical framework that integrates digital capabilities remains absent. This article addresses this gap by examining the evolution of ambient media advertising, synthesizing classical theory with digital advertising principles to propose a new conceptual framework. Through a theoretical synthesis approach, this study redefines ambient media advertising in the digital age as a marketing communication strategy that synergistically leverages physical and digital spaces to create unexpected, personalized, interactive, and contextual advertising experiences, powered by data- and sensor technology. The proposed Digital Integrated Ambient Media (DIAM) model comprises five key elements: Contextual Immersion, Personal Relevance, Interactivity, Surprise Effects, and a Data-Driven Feedback Cycle. The findings offer a robust theoretical foundation for future empirical research and provide practical guidance for designing integrated, experience-based advertising campaigns. The key implications of this study are the expansion of ambient media's conceptual boundaries and the provision of a testable framework for hybrid advertising strategies in contemporary marketing.